2016
DOI: 10.1167/iovs.15-18253
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Binocular Combination of Second-Order Stimuli in Amblyopia

Abstract: Citation: Zhou J, Liu R, Feng L, Zhou Y, Hess RF. Deficient binocular combination of second-order stimuli in amblyopia. Invest Ophthalmol Vis Sci. 2016;57:163557: -164257: . DOI:10.1167 PURPOSE. Sensory imbalances in humans with amblyopia have been well documented using luminance-modulated (first-order) stimuli. However, little is known regarding whether there is a deficient binocular combination in amblyopes for stimuli defined by modulations in contrast (second-order stimuli). To address this, we asked two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…A mblyopia affects 0.5% to 3.6% of the population 1,2 and is one of the most common causes of vision deficit in children. 3 Extensive evidence has demonstrated that amblyopes have poor spatial vision, including visual acuity, vernier acuity, grating acuity, contrast sensitivity, 4 binocular combination, 5 stereoacuity, 6 second-order motion perception, 7 and global form integration 8 in the amblyopic eye. Apart from the spatial visual deficits, amblyopes also experience temporal visual deficit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A mblyopia affects 0.5% to 3.6% of the population 1,2 and is one of the most common causes of vision deficit in children. 3 Extensive evidence has demonstrated that amblyopes have poor spatial vision, including visual acuity, vernier acuity, grating acuity, contrast sensitivity, 4 binocular combination, 5 stereoacuity, 6 second-order motion perception, 7 and global form integration 8 in the amblyopic eye. Apart from the spatial visual deficits, amblyopes also experience temporal visual deficit.…”
mentioning
confidence: 99%
“…The binocular visual deficit in amblyopia has been receiving more recognition, 5,[20][21][22][23][24][25][26] namely, the role of interocular suppression from the fellow eye to the amblyopic eye. 5,20,22,23,27,28 The importance of interocular suppression has been well documented in various binocular spatial visual processes, including binocular phase combination, 5,7 binocular contrast combination, 23 binocular global form integration, 29 and binocular rivalry. 30 These binocular visual deficits have been studied using suprathreshold visual stimuli.…”
mentioning
confidence: 99%
“…We did not examine the mechanism in this study, but we demonstrated that front illumination is an appropriate illumination mode for watching 3D displays. There is much evidence suggesting that illumination of the environment is a modifying factor forocular status [2, 3, 6], visual asthenopia [25, 28], and the contrast modulation of visual cortical cells [29, 30]. Low luminance levels, as in Mode A (complete darkness), would create inadequate viewing conditions and notable variations in the eyes when moving the gaze intermittently between the bright display and darker surroundings and would potentially cause eye strain.…”
Section: Discussionmentioning
confidence: 99%
“…And for patients A1 through A3 and patients A5 through A7, the balance point of the secondorder perceived phase versus interocular modulation depth ratio (PvR) was less than that of the first-order PvR. 2 Here we want to point out that the diagnosis of anisometropic amblyopia for subject A9 may need to be reconsidered. There are not unified anisometropic diopters for the definition of anisometropic amblyopia.…”
mentioning
confidence: 92%
“…We read with great interest the article by Jiawei Zhou et al on second-order deficits in amblyopia. 2 We appreciate the authors' rigorous experimental methods and deliberate mathematical analysis, and we have some of our own thoughts about the authors' work.…”
mentioning
confidence: 99%